Self-confidence and strategic behavior - Charness, Gary; Rustichini, Aldo; van de Ven, Jeroen (Experimental economics : a journal of the Economic Science Association, 2018)
We suggest that overconfidence (conscious or unconscious) is motivated in part by strategic considerations, and test this experimentally. We find compelling supporting evidence in the behavior of participants who send and respond to others’ statements of confidence about how well they have scored on an IQ test. In two-player tournaments where the higher score wins, a player is very likely to choose to compete when he knows that his own stated confidence is higher than the other player’s, but rarely when the reverse is true. Consistent with this behavior, stated confidence is inflated by males when deterrence is strategically optimal and is instead deflated (by males and females) when luring (encouraging entry) is strategically optimal. This behavior is consistent with the equilibrium of the corresponding signaling game. Overconfident statements are used in environments that seem familiar, and we present evidence that suggests that this can occur on an unconscious level.